CORRELATION OF PRE-TRANSPLANT MELD SCORE WITH 30 AND 60 DAYS’ MORTALITY IN PATIENTS OF LIVER TRANSPLANT - Khan, Faryal Riaz Khan; Rao Saad Ali Khan; Khawar Shabbir; Asim Shehzad; Fuad Ahmad Siddiqi; Zara Riaz Khan; Salahuddin; Muhammad Bilal Khattak (Journal of Ayub Medical College Abbottabad, 2024)
Background: The Model for End-Stage Liver Disease (MELD) score, introduced in 2002 by the United Network for Organ Sharing (UNOS), is a vital tool for predicting mortality for liver transplant candidates. Comprising serum creatinine, serum bilirubin, and international normalized ratio (INR), the MELD score includes kidney, liver, and coagulation pathway function, providing a comprehensive prognostic tool. Recent studies suggest broader prognostic implications, extending beyond organ allocation. Despite its benefits, around 15%-20% of patients may not experience accurate survival predictions. Methods: This retrospective single-center study, covering January 2016 to September 2023 with 87 patients, explores the correlation between pre-transplant MELD scores and 30 to 60-day post-transplant survival. Results: Our analysis reveals no significant impact of MELD scores on survival during this period, challenging existing literature (p=0.068). The study underscores the need for nuanced risk assessment beyond MELD scores, considering diverse clinical scenarios and patient-specific variables. Conclusion: Our findings contribute to refining predictive models and advocate for larger-scale investigations, emphasizing a holistic approach to optimize liver transplantation outcomes.